The impact of infrastructure on foreign direct investment in Malaysia - Ahmad, Nor Asma; Ismail, Normaz Wana; Nordin, NurHaiza (TechMind Research, 2015)
FDI is an important contributor to the development and the transformation of the Malaysian economy, particularly in establishing new industries,enhancing production capacity, employment, trade and technological capability. This study aims to investigate the role of infrastructure on FDI in Malaysia from 1980 to 2013. Time series Malaysian data is used to capture the impact of infrastructure on FDI through ARDL method. The results revealed that besides GDP and exchange rate, infrastructure also had positive impact on FDI in Malaysia. The findings suggest that the reduction of business cost through improvement of infrastructure helped to increase competitiveness in attracting FDI.